Tata Kelola Produk Perikanan Penunjang Ekonomi Rakyat - Al Asy'arie, Moh. Asadullah Hasan; Muhammad Hauzan Arifin; Juang Abdi Muhammad (Program Studi Administrasi Fakultas Ilmu Sosial dan Ilmu Politik Universitas Muhammadiyah Bengkulu, 2025)
The fisheries sector in Kaliori Subdistrict, Rembang Regency, has great potential to support the people's economy through capture fisheries, fish farming, and small-scale seafood processing. However, small-scale fishermen face structural constraints such as the dominance of middlemen due to the suboptimal Fish Auction Site (TPI), lack of product innovation, limited access to legal protection programs, and income fluctuations. This community service activity combines demonstrations of value-added fish processing (sausages, nuggets, ekkado) that will be distributed through local MSMEs and legal education based on Law No. 7 of 2016. As a result, participants gained production skills, legal rights knowledge, and collective awareness to improve governance. Strategic recommendations include revitalizing the TPI, strengthening fishermen's cooperatives, optimizing protection programs, enforcing fisheries laws, and providing legal assistance to MSMEs. This simultaneous approach has the potential to improve the welfare of fishermen in a sustainable manner through legal-based economic and institutional strengthening.